Historia XX wieku, totalitaryzm i problem zła - Ceran, Tomasz (Zagłada Żydów. Studia i Materiały, 2015)
The article talks about using term ‘evil’ in professional historical science. The author convinced that in history we can use this term, what’s more, we should research the imagination of ‘evil’ in perpetrator’s minds to understand the genocide and mass murder in 20th century.